From Virtual Carts to Real-Life Purchases: The Role of Digital Technology in Gen Z's Buying Decisions - Isiaka, Gambari Amosa; Amosa, Abdulganiyu Alasela; Brdička, Bořivoj (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: The main objective of this study is to conduct a confirmatory factor analysis on the determinants of shopping behavior, as well as to conduct a difference test analysis to see the differences in shopping behavior between Gen Z and Gen Y. Methodology: The type of data used in this study is primary data, obtained through a questionnaire. The selected samples are Gen Z (aged 10-19 years) and Gen Y (aged 20-35 years) who shop online with e-commerce. The estimation method uses confirmatory factor analysis and independent t-test. Main Findings: The results of the confirmatory factor analysis show that cultural, social, personal, and psychological variables are confirmed as variables that shape shopping behavior. Then the results of the difference test show that Gen Z's shopping behavior is different from Gen Y's shopping behavior. Novelty/Originality of this study: This study offers new insights into how digital technology is bridging the gap between virtual shopping experiences and real-world purchasing decisions among Gen Z consumers. By examining the evolving influence of digital platforms, the study highlights new patterns in Gen Z consumer behavior, providing valuable perspectives for businesses adapting to the digital marketplace.